Pertimbangan Hakim Dalam Penyelesaian Perselisihan PHK - Dalinama Telaumbanua (Eksekusi : Journal Of Law, 2020)
Termination of Employment Relationship (LAY OFFS) is urgent to be discussed primarily related to the reason for termination of employment relationship and also the magnitude of compensation received by workers. Laying offs is one of the problems that can be examined and tried by the Supreme Court. Because there is a Supreme Court ruling No. 1375 K/Pdt. Sus-PHI/2017 relating to the dispute, the writer is interested in knowing and analyzing the judge consideration in the settlement of Termination of Employment Relationship. In answering the issue in this case, the writer used the normative legal research method. The main results of the writer acquired showed that Termination of Employment Relationship was performed by employers because workers were committing violations in the case of frequent late arrivals. The violation is not categorized as severe errors. The lateness of workers can be laid off when they have been set in a work agreement, company regulation or the memorandum of agreement. As the consequence of the termination of employment relationship, the workers get the compensation like separation pay, tenure award money, and the substitution of other rights.